2001
DOI: 10.1021/np000371t
|View full text |Cite
|
Sign up to set email alerts
|

Two New Lactones with Mosquito Larvicidal Activity from Three Hortonia Species

Abstract: The structures of the butenolides 1 and 2, isolated from the endemic plants Hortonia floribunda, H. angustifolia, and H. ovalifolia, collected in Sri Lanka, have been elucidated by spectroscopic analysis. These compounds exhibited potent mosquito larvicidal activity against the second instar larvae of Aedes aegypti.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
32
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(33 citation statements)
references
References 7 publications
1
32
0
Order By: Relevance
“…Lactones, organic cyclic esters, have been also investigated as mosquito larvicides. Two lactones isolated from Hortonia species were able to kill A. aegypti larvae (Ratnayake et al, 2001) and a dehydrocostus lactone isolated from Saussurea lappa essential oil showed strong larvicidal activity (LC50: 2.34 μg/mL) against Aedes albopictus (Liu et al, 2012). Some lactones have been reported as oviposition attractants such as the erythro-6-acetoxy-5-hexadecanolide, which is the major component of oviposition pheromone released in egg droplets of Culex quinquefasciatus .…”
Section: Introductionmentioning
confidence: 99%
“…Lactones, organic cyclic esters, have been also investigated as mosquito larvicides. Two lactones isolated from Hortonia species were able to kill A. aegypti larvae (Ratnayake et al, 2001) and a dehydrocostus lactone isolated from Saussurea lappa essential oil showed strong larvicidal activity (LC50: 2.34 μg/mL) against Aedes albopictus (Liu et al, 2012). Some lactones have been reported as oviposition attractants such as the erythro-6-acetoxy-5-hexadecanolide, which is the major component of oviposition pheromone released in egg droplets of Culex quinquefasciatus .…”
Section: Introductionmentioning
confidence: 99%
“…Naturally derived biocides, such as plant extracts, have received increased attention, and nowadays, more than 2,000 plant species have already been screened as potent insecticides, providing possible candidates to replace the synthetic chemical insecticides particularly for controlling mosquito larvae (El Hag et al 1999;Rahuman et al 2000;Ratnayake et al 2001;Mongelli et al 2002;Trabousli et al 2002Trabousli et al , 2005Yang et al 2002Yang et al , 2003Jeyabalan et al 2003;Cheng et al 2004;Joseph et al 2004).…”
Section: Introductionmentioning
confidence: 99%
“…On 1991 Sukumar et al [12] reviewed the use of natural products derived from 344 different plant species to control mosquito populations. Thus, the plant derived products have received increased attention from scientists and nowadays more than 2,000 plant species have already been screened as potent insecticides providing possible lead candidates to replace synthetic chemical insecticides for controlling mosquito larvae [13][14][15][16][17][18][19][20][21][22][23]. In this regard, plant extracts of the Lamiaceae family present an intriguing case, since they comprise a significant source of potential mosquito control agents [12,21].…”
Section: Introductionmentioning
confidence: 99%